An experiment of a hydropower conversion system based on vortex-induced vibrations in a confined channel. (January 2018) - Dellinger, Nicolas; François, Pierre; Lefebure, David; Mose, Robert; Garambois, Pierre-Andre
Abstract: A hydropower conversion system based on vortex-induced vibrations is investigated experimentally. It consists in a cylinder immerged in a low-velocity flow in a channel (under 1 m/s), which is linked to a variable stiffness spring, so that the natural frequency of the system might be controlled. Current studies report investigations on marine applications. Although rivers or channels constitute a strong energy potential, they are not exploited enough. In this paper, we will investigate the feasibility of such a system implantation in a confined flow in a channel, with important edge effects. We propose a study of the effects of a confined flow on the efficiency of the system. We will highlight feasible improvements, particularly through automatic control strategies (generator behaviour, system's natural frequency). Moreover, we show the strong influence of confinement on the flow topology through velocity field measurements using pulse-pair method. Highlights: A hydro-power conversion system based on vortex-induced vibrations phenomenom is investigated experimentally. We propose a study of the effects of a confined flow on the system efficiency. We highlight feasible improvements, particularly through automatic control strategies. We show strong influence of confinement on the flow topology through velocity field measurements using pulse-pair method.